Aktivitas Larvasida Fraksi N-Heksan Ekstrak Etanol Daun Mengkudu (Morinda citrifolia. L) terhadap Larva Aedes sp. - Rizki Awaluddin; Binti Sholihatin; Nurul Marfu'ah; Solikah Ana Estikomah (Loka Litbang Kesehatan Pangandaran, 2021)
Abstract. Aedes sp. is a vector of the dengue virus that causes Dengue Hemorrhagic Fever (DHF).Larvicides are the optimal method for controlling mosquito development. Temephos is a larvicidalagent of the organophosphate group which is reported to cause side eff ects and ecological hazards,as well as resistance based on reports in several country. This study aims to determine the larvicidalactivity of the n-hexane fraction of Morinda citrifolia leaf ethanol extract on Aedes sp. The compoundgroups in the fraction were identifi ed using TLC through UV light and spray reagents. There were sixtypes of treatment including four concentration fractions (400, 600, 800, and 1000 ppm) as treatment,positive control (temephos 1%) and negative control 1% acetone solution. Twenty-fi ve mosquito larvaeof Aedes sp. tested for each treatment. Larval mortality was recorded and LC50 and LC99 values wereanalyzed using the probit. The results showed that the TLC test of the n-hexane fraction was positivefor terpenoids, anthraquinones, phenols, tannins, and fl avonoids. The results showed that the LC50 andLC99 values were 1040 ppm and 2439 ppm. Therefore, the n-hexane fraction of the ethanol extract hadlarvicidal activity on Aedes sp with li le toxicity.